(untitled) - Marsh, Robert M. (New Jersey, 1976)
While some writers account for Japan's postwar economic "miracle" in terms of a distinctively Japanese, traditional model of social organization, the writers of this study consider Japan's technological growth to have been accompanied by convergence toward modernized social organization. The authors test both of these theoretical models. Their data are derived from a nine-month period of observation, analysis of company records, interviews of personnel, and questionnaire responses from production, staff, and managerial employees in three main Japanese firms. Other firms were visited more briefly. The analysis shows that the most distinctively Japanese variables have less causal impact on performance within a firm than do more universal variables such as employee status, sex, and job satisfaction. The authors test both of these theoretical models. Their data are derived from a nine-month period of observation, analysis of company records, interviews of personnel, and questionnaire responses from production, staff, and managerial employees in three main Japanese firms. Other firms were visited more briefly. The analysis shows that the most distinctively Japanese variables have less causal impact on performance within a firm than do more universal variables such as employee status, sex, and job satisfaction.
Keywords: Industrial sociology,Xã hội học công nghiệp; Japan,Nhật Bản